PENGARUH RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019 - 2023 - Pratiwi, Anggi; Solikah, Mar’atus; Sugeng, Sugeng (Jurnal Riset Akuntansi & Keuangan, 2024)
This research aims to analyze the influence of financial ratios on profit growth. The dependent variable in this research is profit growth, while the independent variable is financial ratios. Data obtained from mining companies in 2019-2023 on the Indonesian Stock Exchange. The sample in this research was 10 companies according to certain criteria. The quantitative research method used is a multiple linear regression analysis technique with a confidence level of 5% to obtain a comprehensive picture of the relationship between one variable and another. The results of the partial test research show that the variables Current Ratio (CR), Debt to Asset Ratio (DAR), Total Asset Turnover (TATO), and Net Profit Margin (NPM) partially have a significant effect on Profit Growth. Based on the results of the simultaneous test, it is known that the variables Current Ratio (CR), Debt to Asset Ratio (DAR), Total Asset Turnover (TATO), and Net Profit Margin (NPM) simultaneously have a significant effect on Profit Growth. It is hoped that the results of this research can be used as a reference for other companies listed on the IDX to pay more attention to financial ratios to increase company profits